World Heritage, Place Making and Sustainable Tourism. Towards Integrative Approaches in Heritage Management. - (:unkn) unknown (StudienVerlag, 2021)
The management of World Heritage Cities and sites is a challenging task. Getting visitor flows and the enormous traffic under control and implementing urban development projects in ways that preserve the integrity and authenticity of cultural heritage requires a high level of expertise, backed by the support of civil society and politics. This book is the result of the 2018 Conference of the Organization of World Heritage Cities, held by the Regional Secretariat for Northwest Europe and North America in Amsterdam, with the theme Heritage & Tourism: Local Communities and Visitors – Sharing Responsibilities. The contributing expert authors – from Africa, the Americas, Asia, and Europe – draw on a range of disciplines to offer wider perspectives, stimulating dialogue among the spheres of heritage, sustainable tourism, and spatial planning. An updated chapter offers perspectives on sustainable tourism also after the COVID-19 pandemic.
Keywords: Weltkulturerbe; Tourismus; Kulturtourismus; Sanfter Tourismus; Nachhaltigkeit; Fremdenverkehrskonzept; Beispielsammlung; International